Implementasi Multimedia Development Life Cycle pada ARbook untuk Pembelajaran Bahasa Inggris di Sekolah Dasar - Harahap, Muhammad Azhari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Currently, the challenge of low learning motivation among elementary school students has become a critical issue requiring innovative solutions. To address this, ARbook was developed with the aim of stimulating students' interest in the learning process through dynamic and interactive visual approaches. In developing ARbook, researchers utilized the Marker-based tracking method to enhance user interaction with learning content. The primary objective of this research was to create a multimedia product capable of optimizing students' learning process and outcomes in an effective and efficient manner. The Multimedia Development Life Cycle (MDLC) methodology was employed as a comprehensive framework for developing the product, encompassing six crucial stages: planning, analysis, design, development, implementation, and evaluation. Through this systematic approach, the research successfully demonstrated that the MDLC method can significantly improve students' academic achievements. The final product, consisting of an integrated application and textbook, was assessed as highly user-friendly and easily accessible to students. This research is expected to make a positive contribution to driving educational media innovation in the future, offering more interactive and engaging educational solutions.